ATS (AUTOMATIC TRANSFER SWITCH) BERBASIS PROGRAMMABLLE LOGIC CONTROLLER CPM1A AUTOMATIC TRANSFER SWITCH (ATS) BASED ON PROGRAMMABLLE LOGIC CONTROLLER CPM1A - Sumardi Sadi; Sri Mulyati (Jurnal Teknik, 2019)
Automatic Transfer Switch (ATS) is a system equipment that can adjust the change of supply of electrical power supply from the main power source from PLN to a backup power source or generator that works automatically with controlling time settings. PLC is used as an ATS system control switch that works automatically and manually in managing the operating time of each generator unit in an effort to supply the load. Where the controller from the PLC works according to the instructions made by the designer in the form of language ladder diagram programming so that the PLN transfer operation time is set during a power outage to the generator can be determined flexibly as desired. The application of PLC-based Automatic Transfer Switch system controller is applied to small scale loads, namely household load with 1 phase voltage capacity from each power source.